Motivational Factors Contributing to Students’ Participation in The English Learning Programs: A Study at MTs. Putri Nurul Haramain Islamic Boarding School Narmada - Riyandani, Rina; Soepriyanti, Henny; Apgrianto, Kurniawan; Waluyo, Untung (Jurnal Ilmiah Profesi Pendidikan, 2024)
This research aims to find out motivational factors contributing the students’ participation in the English learning programs at MTs Putri Nurul Haramain Islamic Boarding School Narmada. This is a case study research using descriptive qualitative design. The participants of this research were 10 students at Cambridge class of MTs Putri Nurul Haramain Narmada. The instruments were observation, and interview. The data analysis was carried out using data reduction, data display, and conclusion drawing and verification. The results show that there are five factors motivated the students in learning English at Learning English Programs which are teachers, activities and material, relevance, feedback, and classroom environment. In addition, the contribution of programs to the students’ motivation are have different perception on the students, Madani Super Camp is has a good contribution on the students’ perception, English Day is has good contribution on the students’ motivation and learning English in the classroom is not good has contribution on the students’ motivation in learning English at English Learning Programs.